STANDARDISATION PROCESSES IN UKRAINE: ACHIEVEMENTS, CHALLENGES, PROSPECTS - Новицький, Кирило; Ващишак, Ірина; Доценко, Євген (SWorldJournal, 2025)
The article offers a comprehensive and updated overview of standardisation processes in Ukraine, combining legal, organisational and sectoral analysis with practical recommendations. The work systematises the achievements of the national standardisation